The use and abuse of cinnabar in Late Neolithic and Copper Age Iberia - Emslie, Steven D. (2022)
In this study, total mercury (THg) was analyzed in archaeological human bone from 23 sites dating to between the Middle Neolithic and the Antiquity. A total of 370 individuals from individual or collective burials was sampled, mostly using cortical bone from the humerus. These individuals were recovered from over 50 different funerary structures ranging from tholoi, pits, caves, and hypogea. Although cinnabar (HgS) is a likely cause of mercury poisoning and toxicity for people exposed to this mineral from mining or use as a paint or pigment, not all sites investigated here had cinnabar associated with the burials or other excavated areas. We found unusual levels of THg in many of the sampled individuals that we assume were caused by exposure to cinnabar in life, and not by diagenetic processes or other exposures to mercury such as through diet, which would only cause negligible accumulation of THg in bone. Our data, based on the largest sampling ever undertaken on contamination of human bone through archaeological evidence, provide a baseline for additional research on cinnabar and its use in Prehistory. Moderate to high levels of THg in human bone are mainly associated with societies dating from the second half of the 4th to late 3rd millennia B.C. (Late Neolithic to Middle Chalcolithic) in southern Iberia. By the Late Chalcolithic and Early Bronze Age, the use of cinnabar decreased significantly and became minimal or absent. The use and abuse of cinnabar appears to have been pervasive throughout the above-mentioned period and particularly between c. 2900-2300 B.C. This occurred in connection with the high symbolic and probably sacred value of the substance, which was sought after, traded, and extensively used in a variety of rituals and social practices.